Carbon footprint and order quantity in logistics - Tian Zhiyong; Huo Lingyu; Shen Guicheng (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Even without economic factors and government regulations, the pressure and motivation of corporation to reduce emissions are still increasing. This is because the key factors for corporation to reduce emissions have been corporate social responsibility and increasing awareness of low carbon among consumers and society not economic trade-off and stringent government regulations. So, the purpose of this paper is to provide quantity methods for the logistics organizations with wish of voluntary reduction and social responsibility to reduce emissions through operations adjustment. Design/methodology/approach: Being difference from the traditional research that takes economic value as objective and carbon footprint as constraint or another source of economic cost, this paper takes carbon footprint as objective directly, order quantity as decision variable. By referring to the traditional economic order quantity model, the paper proposes logistics carbon footprint model which takes transport and inventory into account. Then it solves the model by calculating the values of order quantity, carbon footprint and revenue using the method of optimization. Findings: By solving and comparing the two models, economic order quantity model and carbon footprint model, it gets some results, such as carbon optimization order quantity, the effects of order quantity deviating from economic or carbon order quantity on economic or carbon footprint values, which can give some meaningful insights for corporation to look for reduction opportunities by operations adjustment.Originality/value: The study takes carbon footprint as objective directly and creates the corresponding quantity model. By comparing with the traditional economic order quantity model, it can provide quantity methods and some meaningful insights for the logistics organizations to reduce emissions.
Keywords: 650; inventory; transport; carbon footprint; order quantity